Prevalence of Stable and Successfully Treated Periodontitis Subjects: A Service Evaluation of a Single Hospital Center. - Rattu, Varkha; Nibali, Luigi (International Journal of Periodontics & Restorative Dentistry, 2026)
This evaluation aimed to identify the prevalence of meeting the endpoints for (1) stable periodontitis (defined as: probing pocket depth [PPD] ≤ 4 mm, bleeding on probing [BoP] < 10%, and no BoP at 4-mm PPD sites), (2) endpoints of therapy (no PPD > 4 mm with BoP, no PPD ≥ 6 mm), (3) controlled periodontitis (≤ 4 sites with PPD ≥ 5 mm), (4) PPD < 5 mm, and (5) PPD < 6 mm at the start of supportive periodontal care (SPC). The evaluation also aimed to identify any variables that may affect the achievement of meeting the endpoints. Consecutive patients entering SPC between 2020 and 2022 at Guy's Hospital, London, were assessed. The collected data included periodontal parameters (PPD and full-mouth bleeding and plaque scores) at both baseline and the final active periodontal treatment (APT) visit and were analyzed using SPSS 29.0 for descriptive and quantitative statistics. Logistic regressions utilized univariate and multivarite models to examine associations between clinical variables and outcomes. A total of 141 subjects were included (mean age: 45.4 ± 1.1 years; 64.5% women; 58.9% Caucasian). Most subjects (93.6%) had generalized Stage III/IV periodontitis. At SPC entry, 12.77% of subjects exhibited stable periodontitis, and 48.23% met the endpoints of therapy. Relative percentage changes from baseline to the end of APT in achieving stable periodontitis/endpoints of therapy in teeth were as follows: all teeth (66.25%/90.97%), anterior teeth (81.75%/97.12%), premolars (74.20%/94.69%), and molars (52.40%/86.01%). Regression analyses confirmed associations between age and extent of disease with endpoints but explained limited variance (R2 ≤ 0.267). Periodontal treatment significantly improved clinical parameters at site and tooth levels, though molars demonstrated lower endpoint achievement, highlighting localized treatment challenges. Age and extent of disease influenced outcomes, but predictor variables explained only modest variance, highlighting the complexity of achieving therapeutic success in periodontitis management.